Fatores biopsicossociais da conduta criminosa e sistema de justiça juvenil : avaliação do comportamento antissocial, através da escala hare PCL-YV, de adolescentes femininas em conflito com a lei - Almeida, Rosimar Heleno de (2018)
The present dissertation is aimed at investigating the biopsychosocial aspects of criminal conduct that may be linked to violent behavior. Its objective is to analyze the Juvenile Justice System in order to understand to what extent the state is acting to deal with erratic behavior of teenagers in conflict with the law. In addition to a broad bibliographic analysis, correlating crime themes to psychology, psychiatry, criminology, neurology, sociology and law, this paper presents findings based on empirical research, featuring a sample of 18 female adolescents, authors of homicides and attempted murder, and who are taking correctional measures in a female unit of FASE/RS. The research was carried out through semi-structured interviews, as well as a sociodemographic questionnaire, analysis of medical records and application of the Hare Scale - Psychopathy Checklist: Youth Version (PCL: YV) in order to identify psychopathy traits in the subjects. The results showed that 55.6% of the sample (10 adolescents) had a high score, above 30, evidencing substantial presence of psychopathic traits. This finding indicates that these adolescents are highly probable to re-offend, and a strong tendency to present criminal behavior during their adulthood. It was also found that there is no differentiated treatment for adolescents with antisocial traits. In view of the results obtained and of the gaps found in the Juvenile Justice System, it is suggested the elaboration of programs which take into account the process of guaranteeing the rights and the neuralgic challenges of Brazilian childhood and adolescence; as well as the creation of a treatment that evaluates the biopsychosocial factors that may influence the act of offending, by means of antisocial behavior assessment, through Hare Scale PCL-YV, to be conducted by specialists in Juvenile Justice System units, in order to develop early interventions for adolescents who present psychopathy traces, so that these traits do not consolidate in their adulthood.